2011
DOI: 10.1038/srep00067
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of mesenchymal stem cells from young donors delays aging in mice

Abstract: Increasing evidence suggests that the loss of functional stem cells may be important in the aging process. Our experiments were originally aimed at testing the idea that, in the specific case of age-related osteoporosis, declining function of osteogenic precursor cells might be at least partially responsible. To test this, aging female mice were transplanted with mesenchymal stem cells from aged or young male donors. We find that transplantation of young mesenchymal stem cells significantly slows the loss of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
82
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(85 citation statements)
references
References 50 publications
3
82
0
Order By: Relevance
“…Previously, we demonstrated that transplantation of embryonic fibroblasts treated with PRP could regenerate tissues and extend the life span in aged mice. Tissue regeneration has also been demonstrated through transplantation of muscle-derived stem/progenitor cells to show therapeutic potential for delaying aging-related functional decline in human progenitors [55,4]. Therefore, to delay aging, the stem cell niche and environment are necessary to maintain a young state [31,56].…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Previously, we demonstrated that transplantation of embryonic fibroblasts treated with PRP could regenerate tissues and extend the life span in aged mice. Tissue regeneration has also been demonstrated through transplantation of muscle-derived stem/progenitor cells to show therapeutic potential for delaying aging-related functional decline in human progenitors [55,4]. Therefore, to delay aging, the stem cell niche and environment are necessary to maintain a young state [31,56].…”
Section: Resultsmentioning
confidence: 97%
“…Aging is related to the accumulation of degenerative factors emitted by senescent cells, such as free radicals, proteases, cytokines, and reactive oxygen species (ROS), which lead to increased rates of apoptosis and degeneration [3]. In addition, loss of functional stem cells in aging process would accompany loss of tissue and organ regeneration potential in bone [4], skin [5], brain [6] and hair [7]. Local microenvironments and niche cell interactions are indispensable for maintaining stem cell function.…”
Section: Introductionmentioning
confidence: 99%
“…But practical applications are only just emerging. For example, mesenchymal stem cells from young donors transplanted to aging female mice extended life span, 82 although the effects were small (*16%) when compared to other life-extending interventions like CR. Thus, progress in developing the necessary technologies to intervene in human biology has been modest.…”
Section: Re-engineering Humans For Long Lifementioning
confidence: 99%
“…Interestingly, restoring bone health by transplanting young MSC increased mouse life span significantly [28]. It remains to be determined if restoration of a functional HSC niche and, consequently, improved HSC function play into this life span-extending effect.…”
Section: Hematopoietic Stem Cell Transplantation Assays: Cell-extrinsmentioning
confidence: 99%